AM-37 and ST-36 Are Small Molecule Bombesin Receptor Antagonists - Moody, Terry W.; Tashakkori, Nicole; Mantey, Samuel A.; Moreno, Paola; Ramos-Alvarez, Irene; Leopoldo, Marcello; Jensen, Robert T. (Frontiers in Endocrinology, 2017)
While peptide antagonists for the gastrin releasing peptide receptor (BB2R), neuromedin B receptor (BB1R) and bombesin receptor subtype-3 (BRS-3) exist, there is a need to develop nonpeptide small molecule inhibitors for all three BBR. The bombesin agonist (BA)1 binds with high affinity to the BB1R, BB2R and BRS-3. In this communication, small molecule BBR antagonists were evaluated using human lung cancer cells. AM-37 and ST-36 inhibited binding to human BB2R, BB1R and BRS-3 with similar affinity (Ki = 1.4-10.8 uM). AM-13 and AM-14 were approximately an order of magnitude less potent than AM-37 and ST-36. The ability of BA1 to elevate cytosolic Ca2+ in human lung cancer cells transfected with BB1R, BB2R and BRS-3 was antagonized by AM-37 and ST-36. BA1 increased tyrosine phosphorylation of the EGFR and ERK in lung cancer cells which was blocked by AM-37 and ST-36. AM-37 and ST-36 reduced the growth of lung cancer cells which have BBR. The results indicated that AM-37 and ST-36 function as small molecule BBR antagonists.